Welding safety - Safetycare Australia (Australia : Safetycare Australia, 1992)
Presents the critical safety hazards in welding that different at each and every location and there is a need to approach welding as unique trade requiring through evaluation of the factors involved every day of operation
A skills education program
VCD format
Keywords: Welding -- Safety measures; Welding; Industrial safety; Industrial accidents -- prevention